The Gut–Skin Axis: The Role of Intestinal Microbiota in Acne, Psoriasis and Atopic Dermatitis: A Narrative Review - Pączek, Adrian Jan; Kowalczyk, Aleksandra; Hofman, Julia; Staniszewska, Wiktoria; Dyczek, Paweł; Bednarek, Ilona; Lach, Sylwia (Journal of Education, Health and Sport, 2025)
Background. The gut–skin axis links intestinal dysbiosis with chronic inflammatory skin diseases. Acne vulgaris, psoriasis and atopic dermatitis have been associated with altered gut microbial diversity, metabolite production, barrier function and immune regulation. Objective. To summarize current evidence on the role of intestinal microbiota in the pathogenesis and potential management of acne vulgaris, psoriasis and atopic dermatitis, with emphasis on gut–skin mechanisms and microbiota-targeted interventions. Methods. A narrative review of PubMed and PubMed Central (2015–2025) was performed using terms related to the gut–skin axis, intestinal microbiota, acne, psoriasis, atopic dermatitis, dysbiosis and probiotics. Human and translational studies, systematic reviews, meta-analyses and high-quality narrative reviews on gut microbiota in these conditions were included; 20 publications were synthesized qualitatively. Results. Across the included studies, gut dysbiosis in all three diseases was characterized by reduced microbial diversity, loss of short-chain fatty acid-producing commensals and enrichment of pro-inflammatory taxa. In acne, these changes correlated with systemic inflammation and sebaceous activity; in psoriasis, with Th17-driven inflammation and associated comorbidities; in atopic dermatitis, with early-life immune dysregulation and barrier dysfunction. Several clinical trials reported modest, strain-dependent improvements in disease severity with Lactobacillus- and Bifidobacterium-based probiotics. Conclusions. Available data support a mechanistic link between intestinal microbiota and inflammatory skin diseases. Gut dysbiosis appears to contribute to immune polarization and barrier impairment, while microbiota-modulating strategies show promise as adjunctive therapies. Further well-designed trials are needed to clarify causality and to define effective, standardized microbiota-based interventions.